THE CONCEPT AND SPECIFIC FEATURES OF A FREE ECONOMIC ZONES (World Bulletin of Management and Law, 2022)
This article covers the most important aspects of free zones and the history of their common origin. From the history of its initial formation to the present day, their appearance and specific features have been studied. The types of existing free-trade zones, nomenclature and legal basis of existing free economic zones in the Republic of Uzbekistan as a separate state are presented
Keywords: Free economic zone; economic upsurge; foreign economic relations; customs duties.